Pharmacist’s role in the system of palliative and hospice care in Ukraine and Poland (Journal of Medical Science, 2014)
Introduction. The efficient pharmacotherapy is an important part of palliative and hospice care, and requires a multidisciplinary approach to the patients. The pharmacist, as the member of the multidisciplinary therapeutic team, is responsible for performing pharmaceutical care, which provides safe and efficient treatment. The aim of the research was to conduct a comparative research about the status of palliative and hospice care and role of the pharmacist (clinical pharmacist) in Ukraine and Poland. Material and methods. It was a questionnaire survey conducted in Ukraine, as well as analysis of information sources associated with this subject. The questionnaire was developed on the basis of similar study conducted in Poland. It consisted of 15 multiple-choice questions addressed to head physicians and doctors in Ukraine. The obtained results were compared to the results of the mentioned above Polish study. Results. Eight head physicians and 22 doctors (30 questionnaires) from 13 palliative and hospice care institutions in Ukraine responded to the survey. It has been found that almost half in Ukraine (43%) believed that the pharmacist should be a mandatory member of a multidisciplinary team, because of his/her significant role in drug management in hospice. Conclusion. A multidisciplinary approach to satisfying of patients’ needs in palliative and hospice care has a great significance. Results of the study testify to the importance of including the pharmacists into the multidisciplinary team.